A Critical Review on Medicinal Plants for the Treatment of Bronchial Asthma - Joshi, Krupa (Asian Journal of Pharmaceutics (AJP), 2023)
The current study recorded cultural groups’ historical education of medicinal herbs and plants used to treat respiratory illnesses like asthma in India. The current study depends on an overview of the scientific literature and contains specific information about how different tribal communities in India use plants and their components to control bronchial asthma. Asthma is a widespread condition that is becoming more frequent all over the world, with the highest frequency in industrial nations. Plants have been used as outstanding sources of medicine throughout antiquity. As a result of the detrimental effects of current asthma medication, individuals are exploring complementary and alternate medicines to cure their asthma. Plants are used to heal a number of human ailments in ayurveda and other Indian literature. There are around 45,000 species of plants in India, with many of them claiming therapeutic benefits. Recent research on plants that have been mentioned or used traditionally for asthma has demonstrated anti-asthmatic, anti-histaminic, and anti-histamine effects. Different herbs and extracts from them provide anti-asthmatic, anti-allergic, and anti-cholinergic characteristics, according to this chapter.